CHECKLIST OF HELMINTHS ASSOCIATED WITH CONTINENTAL TESTUDINES FROM SOUTH AMERICA - Mascarenhas, Carolina S. (2021)
This study collected records of 135 taxa of parasitic helminths (Nematoda, Trematoda, Cestoda, Monogenoidea and Acanthocephala) and ectosimbionts (Temnocephalida) associated with continental Testudines from South America. Eighty-nine helminths were identified at the species level while others were identified up to genus or family levels. The greatest diversity of helminths associated with Testudines was reported in Brazil. Chelidae was the family with the largest number of helminth species. Regarding the conservation status, 17 Testudines species with helminth records are cited in the IUCN Red List of Threatened Species. Knowledge of helminth biodiversity and of relations between these organisms and Testudines can provide important data on host biology. Therefore, information generated by studies of helminths can contribute to research which aims at the conservation of organims and their habitats.